Assessing agricultural trade comparative advantage of Myanmar and its main competitors: Findings from UN Comtrade - Zhang, Huaqi; Chen, Kevin Z. (International Food Policy Research Institute, 2019)
This paper aims to provide a better understanding of Myanmar’s agricultural export performance against its competitors in different regions and determine the policy actions for improving Myanmar’s export performance. The normalized revealed comparative advantage (NRCA) index is computed to compare the agricultural competitiveness between Myanmar and its competitors from 2007 to 2016. The results show that: 1) Myanmar’s agricultural export sector enjoys comparative advantage in the global market, but it is not competitive when compared with its major competitors; 2) Myanmar reveals a high level of NRCAs in black gram & pigeon peas, natural rubber, sesame seeds, rice, and frozen fish, while it has low NRCAs in crustaceans and dried fruits; and reveals no comparative advantage in bananas, fish fillets, maize, nuts, and watermelon in certain years. Three major policy implications are drawn, including diversifying Myanmar’s export portfolio, strengthening export promotion and development, and attracting foreign direct investment to upgrade the cross-border value chain.